INTRAOPERATIVE ULTRASOUND NAVIGATION IN SURGICAL TREATMENT OF UTERINE MYOMAS - N. V. NAUMOVA; E. A. BOLDOVSKAYA; V. V. MAKUKHINA; V. A. KRUTOVA (Кубанский научный медицинский вестник, 2018)
Aim. Improvement of the results of surgical treatment of uterine myomas using intraoperative ultrasound navigation.Materials and methods. 74 women with uterine myomas under supervision were examined and operated with endoscopic access using pre- and intraoperative methods of echographic diagnostics. The control group consisted of 74 patients with uterine myomas who underwent traditional ultrasound examination of pelvic organs before and after the operation.Results. The use of intraoperative transvaginal and laparoscopic echography reduces the time of surgical revision, reduces the frequency of intra- and postoperative complications, and the frequency of relapses in the postoperative period.Conclusion. Intraoperative ultrasound navigation is an important research method to clearly define the scope of the surgery, ensure its safety, and also more accurately assess the adequacy of the surgical treatment performed.